2011
DOI: 10.1530/eje-10-0761
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and behavioural aspects in children and adolescents with congenital hypothyroidism diagnosed by neonatal screening: comparison between parents' and children's perceptions

Abstract: Objective: To compare the psychological adjustment and behaviour of congenital hypothyroidism (CH) children and their parents with a control group. Study design: A cross-sectional study was carried out with 84 CH subjects diagnosed by neonatal screening (range 2.7-18.6 years), subdivided into four age groups: group 1 (2-5 years); group 2 (6-10 years); group 3 (11-13 years); and group 4 (14-18 years) and was compared with an age-matched control group. Patients were assessed using two questionnaires: Child Behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Only minor behavioral differences between patients and the reference population have been reported (34,35,36). The higher percentage of CH patients than of their healthy peers still living with parents may reflect lower patient maturity and autonomy, as reported for young adult patients with chronic conditions of childhood onset (37).…”
Section: Cognition Behavior and Socioeducational Attainmentmentioning
confidence: 92%
“…Only minor behavioral differences between patients and the reference population have been reported (34,35,36). The higher percentage of CH patients than of their healthy peers still living with parents may reflect lower patient maturity and autonomy, as reported for young adult patients with chronic conditions of childhood onset (37).…”
Section: Cognition Behavior and Socioeducational Attainmentmentioning
confidence: 92%
“…There was substantial variation between these studies in sample size and in the approach to data analysis and presentation. Ten studies analyzed the level of agreement between child and parent scores through correlations 11,33,40,[45][46][47][48][49][50][51] (Pearson or Spearman rank correlation or intraclass correlation coefficients), whereas 11 used other approaches in which there was no statistical analysis of self-proxy agreement reported 31,34,[52][53][54][55][56][57][58][59][60] (Table 3). Only 1 study analyzed the magnitude of the disagreement or agreement, taking into account the average SDs of the child and parent scores (effect size), the direction of self-proxy difference, and the factors affecting it.…”
Section: Studies Comparing Self-reports and Proxy Reportsmentioning
confidence: 99%
“…19 Various studies including a study by Nicoletta Bisacchi had shown that there is a definite risk of behavioural problems in children with congenital hypothyroidism again pointing for early diagnosis, prompt treatment and regular and systematic follow up for a better outcome in these children. 20…”
Section: Discussionmentioning
confidence: 99%